Chapter 5 : Assessing risk of bias as a domain of quality in medical test studies - Santaguida, P. Lina. (2013)
Assessing methodological quality is a necessary activity for any systematic review, including those evaluating the evidence for studies of medical test performance. Judging the overall quality of an individual study involves examining the size of the study, the direction and degree of findings, the relevance of the study, and the risk of bias in the form of systematic error, internal validity, and other study limitations. In this chapter of the Methods Guide for Medical Test Reviews, we focus on the evaluation of risk of bias in the form of systematic error in an individual study as a distinctly important component of quality in studies of medical test performance, specifically in the context of estimating test performance (sensitivity and specificity). We make the following recommendations to systematic reviewers: 1) When assessing study limitations that are relevant to the test under evaluation, reviewers should select validated criteria that examine the risk of systematic error, 2) categorizing the risk of bias for individual studies as “low,” “medium,” or “high” is a useful way to proceed, and 3) methods for determining an overall categorization for the study limitations should be established a priori and documented clearly.